Value relevance of managed earnings in Indian firms: an impact analysis of IFRS convergence using dynamic panel models - Gomes, Lorraine Rayelle; Costa, Juao C. (Serbian Journal of Management, 2024)
The study explores the relationship between earnings management and value relevance of accounting information of Indian listed firms by investigating three different modes of earnings management – total, short-term and long-term discretionary accruals. Additionally, the study investigates the impact of the converged International Financial Reporting Standards (IFRS), known as Indian Accounting Standards (IndAS), on earnings management which in turn influences value relevance. This study is the first in India to analyse the differential effects of short-term and long-term earnings management on value relevance and to address the endogeneity issue in the price value relevance model through dynamic panel modelling while controlling for the use of the IndAS. The study finds a significant effect of both short-term and long-term accruals management on value relevance and a positive influence of IndAS on the relationship between earnings management and firm value